Subjective assessment of occupational stress and mental health of nurses during the Covid-19 pandemic period - Kowalczuk, Krystyna; Tomaszewska, Katarzyna; Chilińska, Joanna; Krajewska-Kułak, Elżbieta; Sobolewski, Marek; Hermanowicz, Justyna M. (Frontiers in Psychiatry, 2023)
Health status, sickness absence, and nurses' attrition have a direct impact on the quality of care provided and patients' health outcomes. The Covid-19 pandemic exacerbated issues that existed within the Polish healthcare system prior to the pandemic, including staff shortages, low wages, and system inadequacies. The aim of this study was to investigate how nurses during the Covid-19 pandemic period rated the burdensomeness of job characteristics and their mental health status, as well as the correlations between factors directly caused by the Covid-19 pandemic and nurses' subjective assessments of job characteristics and mental health. The cross-sectional study was conducted in January 2022, in Poland and involved 796 registered nurses working in hospitals. Despite the pandemic's sweeping societal effects, this research finds limited alteration in nurses' perceptions of job stress and self-assessed mental health. Factors such as contact with infected patients, quarantine, and isolation do not appear to substantially modify mental health perceptions among nurses. Intriguingly, nurses subjected to COVID-19 testing report heightened stress and compromised mental health. This study underscores the intricate interplay of diverse factors shaping nurses' well-being, advocating for judicious implementation of pandemic-related measures to alleviate potential detrimental effects on mental health.